The Effect Of Work Discipline And Incentives On Employee Performance Through Motivation Of Employees In The Regional Secretariat Of Lebak District - Ubaidillah, M. Farhan; Wiguna, Wahyu; Suparmoko, Muhammad (Jurnal Economic Resource, 2025)
The performance of Regional Secretariat employees is a strategic factor in improving the quality of public services. However, discipline issues and dissatisfaction with incentives are still found in the Regional Secretariat of Lebak Regency, potentially reducing work motivation and impacting employee performance. This study aims to analyze the influence of work discipline and incentives on employee performance, with motivation as a mediating variable. The research method uses a quantitative approach with Partial Least Square (PLS) analysis techniques. Data were collected through distributing questionnaires to employees of the Regional Secretariat of Lebak Regency, then analyzed to test the direct and indirect effects between variables. The results show that work discipline and motivation have a significant positive effect on employee performance. Conversely, incentives do not have a direct effect on employee performance, although through motivation, incentives can have an indirect effect. These findings emphasize the importance of strengthening a culture of discipline and work motivation as a more effective strategy than relying solely on incentive policies. Thus, human resource management within the Regional Secretariat of Lebak Regency needs to be more directed at improving discipline and empowering internal employee motivation